Customer relationship management (CRM) experiences of Business-to-Business (B2B) marketing firms: A qualitative study - Andy Fred Wali (Taylor & Francis Group, 2016)
This study explored customer relationship management (CRM) experiences of business-to-business (B2B) marketing firms in the mobile telecommunications sector using the qualitative focus group approach and the study drew on the resource-based view. The qualitative focus group approach was adopted and two focus groups were held, which comprise 10 staff of mobile telecommunications B2B firms. The interview data were analysed using thematic template and content analysis, respectively, with the aid of Nvivo 10 software. The study found four emerging themes, which characterise CRM experiences of mobile telecommunications B2B marketing firms and they include: resource commitment; product knowledge development; customer orientation behaviour; and B2B service personalisation. The study concluded that the nature of relationship between B2Bs and their principal operators is product/sale oriented rather than customer oriented. This study validates the RBV and offered recommendations based on its thematic findings.